Structures Suggestive of Carotid Artery Calcifications and Their Prevalence on Digital Panoramic Radiographs - Adad, Luana P.V.; Oliveira, Lucas B.; Orestes, Sther G.; Franco, Ademir; Makeeva, Irina; Vetter, Flávia; Fernandes, Ângela (UI Scholars Hub, 2019)
Objectives: To investigate prevalence of carotid artery calcifications via digital panoramic radiographs of patientswho underwent dental treatment. Methods: Panoramic radiographs of 12.687 patients who underwent dentaltreatment at a federal university, were collected (male, n = 5.169, 40.7%; female, n = 7.518, 59.3%). Patients wereaged 2–87 years (mean age, 34 years). Radiographs were obtained using a digital device. Two trained examinersanalyzed the images with an imaging software package. Radiopaque images in the C3 and C4 cervical vertebraeregion were searched for. Statistical outcomes were analyzed based on their association with sex and age. Results: The prevalence rate of carotid artery calcifications was 1.8% (n = 227). We identified unilateral (n = 140, 61.67%)and bilateral (n = 87, 38.33%) calcifications. Prevalence and sex (130 females, 97 males) were not statisticallysignificant (p > 0.05). We observed calcifications predominantly in patients aged 50–60 years (p < 0.05). Conclusion: Awareness by physicians and dentists of the possible presence of carotid artery calcifications on digital panoramicradiographs is necessary. To optimize the risk management of vascular diseases, asymptomatic patients in theirfifties or sixties must receive additional attention because panoramic radiographs may lead to diagnosis.